2017
DOI: 10.1111/jvs.12512
|View full text |Cite
|
Sign up to set email alerts
|

Testing a general approach to assess the degree of disturbance in tropical forests

Abstract: Questions Is there any theoretical model enabling predictions of the optimal tree size distribution in tropical communities? Can we use such a theoretical framework for quantifying the degree of disturbance? Location Reserve of Yangambi, northeast region of the Democratic Republic of Congo. Methods We applied an allometric model based on the assumption that a virtually undisturbed forest uses all available resources. In this condition, the forest structure (e.g. the tree size distribution) is theoretically pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Therefore, knowing how leaf area (and thus productivity) scales as individual trees increase in size, together with the assumption that forest resource use is always maximal (meaning that a community is saturated with individuals, whether it is composed of many small or few large individuals), allows prediction of the slope of tree size distributions in any community (Simini et al , 2010; Anfodillo et al , 2012). Deviation from the predicted distribution can even be diagnostic of forest disturbance (Coomes et al , 2003; Sellan et al , 2017). This energy equivalence expectation, supported here by constant conductance per unit leaf area, represents a potential link between hydraulics, stand productivity, and the shaping of optimal canopy height and density by microsite (Eagleson, 1982; Cabon et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, knowing how leaf area (and thus productivity) scales as individual trees increase in size, together with the assumption that forest resource use is always maximal (meaning that a community is saturated with individuals, whether it is composed of many small or few large individuals), allows prediction of the slope of tree size distributions in any community (Simini et al , 2010; Anfodillo et al , 2012). Deviation from the predicted distribution can even be diagnostic of forest disturbance (Coomes et al , 2003; Sellan et al , 2017). This energy equivalence expectation, supported here by constant conductance per unit leaf area, represents a potential link between hydraulics, stand productivity, and the shaping of optimal canopy height and density by microsite (Eagleson, 1982; Cabon et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the tropics, scaling exponents from crown allometric relationships have been shown to vary between forests and savannas, with savanna tree crowns tending to be larger for a given stem diameter than those of forest trees at the species scale (Archibald & Bond, 2003) and the site scale (Shenkin et al., 2020). However, the scaling exponents of crown allometric relationships do not change when comparing three neighbouring forest typologies (mixed forests, edge forests and regrowth forests) that have different light availability (Sellan et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This trend is more pronounced in conifers, therefore we could expect Norway spruce to grow comparatively fewer leaves at higher elevations. However, other studies have found little variations in the relationship between crown volume and tree height in forests with different compositions, disturbance histories, and elevations, but within limited latitudinal ranges [35][36][37]. This highlights the need for more field-based research on the drivers of tree structural balance and allocation patterns.…”
Section: Introductionmentioning
confidence: 97%
“…We also expect that allometric relationships, given their fundamental importance in determining tree fitness, are constant along the gradient. This hypothesis is based on the general quantitative theory of forest structure and dynamics [38,39] and is backed by existing studies providing evidence of the stability of allometric relationships despite environmental variations [33,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation